Sistema de detección de fraude en la operación de Rappi basado en grafos y algoritmos de machine learning (2020)
In recent years there has been a significant evolution in the realization of non-face-to-face operations, that is, those in which the physical presence of the client or user is not necessary and in which digital transactional channels, such as it is the Internet and the use of Mobile Telephony. This growing trend in making digital payments for the purchase and sale of products and services through the Internet, an activity that is known by the name of eCommerce, brings with it the appearance of Fintech companies that offer in a disruptive way to their potential customers, a series of innovative financial products and services through the use of new technologies. Rappi is one of the most recognized Fintech companies that is part of the aforementioned digital payments ecosystem, which works through an application installed on Mobile Phones and its objective is to connect customers with the various commerce establishments that accept digital payments...